Design And Development Of Wear Testing Analysis On Cylinder Head Valve - S. W., Tan; Mohamad Fadli, Zolkipli; M., Rosyazwan; N., Hafizah; M., Shahrel (2015)
These projects are aimed to design and development of wear testing analysis on cylinder head valve. The cylinder head sits above the cylinders on top of the cylinder block. It closes in the top of the cylinder, forming the combustion chamber. This joint is sealed by a head gasket. In most engines, the head also provides space for the passages that feed air and fuel to the cylinder, and that allow the exhaust to escape. The head can also be a place to mount the valves, spark plugs, and fuel injectors. The project is based on study the design, mechanical movement and component of head valve and also to analysis the stress and strain of a valve by using finite element method. The exhaust valve system of combustion engines experiences a very complex contact situation of frequent impact involving micro sliding, high and varying temperatures, complex exhaust gas chemistry and possible particulates, etc. In addition, the tribological situation in the exhaust valve system is expected to become even worse due to strict future emission regulations, which will require enhanced combustion and fuels. This will substantially reduce the formation of combustion products that might ease the contact conditions by forming tribofilms on the contacting surfaces. The lack of protective films is expected to result in increased wear of the contact surfaces. The result will present by the successful of the project mechanisms to run and also the simulation of the mechanisms.